2019
DOI: 10.1111/imm.13100
|View full text |Cite
|
Sign up to set email alerts
|

CD93 is a cell surface lectin receptor involved in the control of the inflammatory response stimulated by exogenous DNA

Abstract: Summary Bacterial DNA contains CpG oligonucleotide (ODN) motifs to trigger innate immune responses through the endosomal receptor Toll‐like receptor 9 (TLR9). One of the cell surface receptors to capture and deliver microbial DNA to intracellular TLR9 is the C‐type lectin molecule DEC‐205 through its N‐terminal C‐type lectin‐like domain (CTLD). CD93 is a cell surface protein and member of the lectin group XIV with a CTLD. We hypothesized that CD93 could interact with CpG motifs, and possibly serve as a novel r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 29 publications
0
24
0
Order By: Relevance
“…CD93 is a transmembrane glycoprotein that is expressed primarily in endothelial cells but also in granulocytes, monocytes, platelets and stem cells [66]. The protein is involved in several processes of innate immunity, such as adhesion, phagocytosis and inflammation [67]. In the context of the latter, CD93 may act as a plasma membrane receptor for DNA for delivery to endosomal TLR9.…”
Section: Discussionmentioning
confidence: 99%
“…CD93 is a transmembrane glycoprotein that is expressed primarily in endothelial cells but also in granulocytes, monocytes, platelets and stem cells [66]. The protein is involved in several processes of innate immunity, such as adhesion, phagocytosis and inflammation [67]. In the context of the latter, CD93 may act as a plasma membrane receptor for DNA for delivery to endosomal TLR9.…”
Section: Discussionmentioning
confidence: 99%
“…Another peculiarity of porcine pDC was found to be shared between blood and lymphoid tissue: the high expression of complement-related genes such as C2, C3 , or CD93 . Interestingly, CD93 was shown to be involved in delivery of CpG ODN to endosomal TLR9 ( 49 ) and could be an interesting way of targeting and activating porcine pDC. Both porcine cDC subsets from lymphoid tissues also showed expression of markers that were not expressed on their blood counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…Although McGreal et al [ 7 ] have shown that the protein does not bind C1q in physiological state, novel studies have confirmed the association of CD93 with phagocytosis of apoptotic cells [ 8 , 9 ]. In addition, CD93 has been shown to be involved in angiogenesis, endothelial cell adhesion, and inflammatory response [ 4 , 5 , 10 , 11 ]. Increased expression of membrane CD93 was observed on activated macrophages along with increased concentrations of sCD93 in plasma [ 5 ].…”
Section: Introductionmentioning
confidence: 99%